Validation of the sleep disturbance scale for children (SDSC) in infants and toddlers from mainland China - Chen, Xianrui; Xu, Ping; Chen, Yanhui; Chen, Shan; Yao, Yonghua; Lin, Xiaoxia (Frontiers in Psychiatry, 2022)
A Chinese version of the sleep disturbance scale for children (SDSC) has been validated for 5 to 16-year olds. However, the assessment tool of sleep disturbance in infants and young children from mainland China is relatively rare and limited, and clinicians cannot objectively, accurately, and comprehensively screen for early detection and intervene to treat them. Objective: To evaluate the reliability and validity of SDSC among infants (aged 6 months to 36 months) in mainland China, and to provide a reference for expanding the application of the SDSC for the Chinese infants (SDSC-I). Method: From April to November 2021, parents of infants from Fuzhou, Quanzhou, Longyan, Sanming and Nanping in Fujian Province completed the SDSC which is specifically for infants and toddlers. The reliability and validity of the scales were estimated by item analysis, standard Cronbach's alpha coefficient, exploratory factor analysis (EFA), confirmatory factorial analyses (CFA) and other measurement characteristics. Results: 432 out of 469 samples were valid. Through item selections and exploratory factory analysis, the SDSC-I concluded 6 dimensions (Disorders of Initiating Sleep, Disorders of Maintaining Sleep, Sleep Hyperhidrosis, Sleep Breathing Disorders, Parasomnias, and Non-Restorative Sleep and Excessive Somnolence) including 23 items. Cronbach's α coefficient of the scale was 0.863, for the 6 dimensions were within 0.576-0.835. The values of parameters for content validity of the scale were: IR=0.87, I-CVI>0.78, Kappa value>0.74, S-CVI/UA=0.87, S-CVI/Ave=0.98. Principal component analysis revealed that, the KMO value was 0.84, the factor loading of items ranged from 0.328-0.849, with 6 factors of eigenvalue >1, which could explain 58.274% of the total variance. The results of the confirmatory factor analysis showed: χ2/DF was 3.556, RMSEA was 0.077, CFI was 0.809, and SRMR was 0.070. Conclusion: The SDSC-I has been proved to be reliable and valid, and it can assess the sleep problems of infants in a comprehensive and detailed manner. Therefore, the scale is useful for early screening and adetection of sleep disorders by clinicians, and is worthy of popularization and application.